Clínica Médica e Cirúrgica de Pequenos Animais. - Nunes, Karlla de Freitas (Universidade Federal do Tocantins, 2023)
The fellowship was conducted at the Veterinary Hospital of the School of Veterinary Medicine and Animal Science of the Federal University of Goias (UFG-HV-EVZ) from April 22nd to June 25th, totaling 348 hours. In this period, 145 clinical cases were treated. Trainees were required to follow the monitor residents in attendance, performing anamnesis, physical examination, collection of biological samples, and to monitor surgical procedures, from preoperative until release the patient. This report aims to describe the activities performed at the institution and describe three clinical case accompanied.